Dioscorea alata: Potensinya Sebagai Bahan Pangan Alternatif dan Obat Tradisional - Marina Silalahi; Stephani Hizkia Samosir (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Dioscorea alata is a species belonging Dioscoreaceae has been long been used as a source of carbohydrates by various local communities in Indonesian, but not use as traditional medicine. This study aims to explain the potential of D. alata as an alternative food and traditional medicine. The research method is literature study of various research that published online, especially on google scholar, using the keywords D. alata and uses D. alata. The information obtained thus explains the potential use of D. alata as a healthy food ingredient and its use as a traditional medicine. Disocorea alata has long been traded in various traditional markets used as food and traditional medicine. Based on ethnobotanical research, D. alata is used treat hypertension and diabetes mellitus. Bioactivity of D. alata is anti-hypertension, anti-inflammatory, estrogenic and immunomodulator. Dioscorea alata has the potential to support food security programs in Indonesia because it contains carbohydrates, proteins, minerals and vitamins. Dioscorin is a protein compound found in D. alata tubers which is associated with its antihypertensive and estrogenic activity.